Samoa : Request for Disbursement Under the Rapid-Access Component of the Exogenous Shocks Facility; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Samoa. (IMF Staff Country Reports; Country Report ;, 2010)
This paper discusses a request from Samoa's authorities for a Disbursement Under the Rapid-Access Component of the Exogenous Shocks Facility (ESF-RAC). The tsunami that hit Samoa on September 29, 2009 has undercut Samoa's economic resilience and prospects for a quick recovery from the global recession. Real GDP is likely to contract in 2010. The authorities have requested a disbursement equivalent to 50 percent of quota (SDR 5.8 million) under the IMF's ESF-RAC. IMF staff supports the request on Samoa's low public debt and credible commitment to sound macroeconomic policies.